Spin-orbit torque magnetic random access memory
By using the nickel-tungsten alloy layer as a spin current source in the spin orbit moment magnetic random memory and adjusting its composition proportion and structure, the problem of insignificant spin Hall effect in the prior art is solved, the effect of reducing the write current is achieved, and the performance and application range of the memory are improved.
Patent Information
- Application Number
- CN202311115017.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
AI Technical Summary
In the existing spin orbit moment magnetic random memory (SOT MRAM), heavy metal materials are difficult to match the body-center cubic (BCC) crystal structure of ferromagnetic materials, resulting in a spin Hall effect that is not significant and cannot effectively reduce the write current.
The nickel tungsten alloy layer is used as the spin current source, and the composition ratio and structure of the nickel tungsten alloy layer are adjusted to match the structure of the ferromagnetic free layer, thereby increasing the spin Hall angle and reducing the write current.
By increasing the spin Hall angle, the need for write current is significantly reduced, the performance and efficiency of magnetic random memory is improved, and its application range is expanded.
Smart Images

Figure CN119545808A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a magnetic random access memory technology, and in particular to a spin orbit torque magnetic random access memory (SOT MRAM). Background Art
[0002] With the development of artificial intelligence, electric vehicles, and big data, the demand for memory is gradually increasing. Since the current mainstream memory such as DRAM, SRAM, etc. are all volatile memories, they must be continuously powered to maintain data, so too much energy is consumed in data storage.
[0003] In order to reduce energy consumption, non-volatile memory such as MRAM and RRAM has gradually gained attention. In the development of MRAM, it can be mainly divided into three generations according to different writing methods: writing using magnetic field, writing using spin transfer torque (STT), and writing using spin orbit torque (SOT).
[0004] In the third generation SOT MRAM, heavy metal materials are usually used as the source of spin current to achieve a good spin Hall effect. However, since the crystal structure of ferromagnetic materials in MRAM is mostly body-centered cubic (BCC), existing heavy metal materials are difficult to match it, resulting in a weak spin Hall effect and unable to reduce the write current. Summary of the invention
[0005] The present invention is directed to a spin-orbit moment magnetic random access memory, which can increase the spin Hall angle and thus reduce the write current.
[0006] According to an embodiment of the present invention, a spin-orbit torque magnetic random access memory comprises at least a spin current source alloy layer, a ferromagnetic free layer and an insulating layer. The spin current source alloy layer is a nickel-tungsten alloy layer, the ferromagnetic free layer is located on the spin current source alloy layer, and the insulating layer is located on the ferromagnetic free layer.
[0007] In the spin-orbit torque magnetic random access memory according to an embodiment of the present invention, the nickel-tungsten alloy layer is in direct contact with the ferromagnetic free layer.
[0008] In the spin-orbit torque magnetic random access memory according to an embodiment of the present invention, the nickel-tungsten alloy layer contains more than 30 at % of tungsten.
[0009] In the spin-orbit torque magnetic random access memory according to an embodiment of the present invention, the nickel-tungsten alloy layer contains less than 90 at % of tungsten.
[0010] In the spin-orbit torque magnetic random access memory according to an embodiment of the present invention, the nickel-tungsten alloy layer has several regions with different polarities.
[0011] In the spin-orbit torque magnetic random access memory according to an embodiment of the present invention, the shapes of the above-mentioned several regions include block, line or a combination thereof.
[0012] In the spin-orbit torque magnetic random access memory according to the embodiment of the present invention, the above-mentioned several regions each have a different nickel-tungsten composition ratio.
[0013] In the spin-orbit torque magnetic random access memory according to an embodiment of the present invention, the above-mentioned nickel-tungsten alloy layer is a multilayer film structure, which is composed of several sub-layers. The flipping behavior of the ferromagnetic layer is controlled by controlling the different nickel-tungsten composition ratios in each sub-layer.
[0014] In the spin-orbit torque magnetic random access memory according to an embodiment of the present invention, the number of film layers of the multi-layer film structure may be 2 to 10 layers.
[0015] Based on the above, the present invention uses a nickel-tungsten alloy that can match the ferromagnetic free layer structure as a spin current source, thereby increasing the spin Hall angle and reducing the write current. Moreover, by adjusting the alloy ratio of different regions in the nickel-tungsten alloy layer, the device properties, such as the spin Hall angle flip polarity, etc., can be adjusted. Therefore, the application of the spin-orbit moment magnetic random access memory of the present invention can be more extensive.
[0016] In order to make the above features and advantages of the present invention more clearly understood, embodiments are given below with reference to the accompanying drawings for detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The figure is a cross-sectional schematic diagram of a spin-orbit torque magnetic random access memory according to an embodiment of the present invention.
[0018] Figure 2 It is a three-dimensional schematic diagram of a spin-orbit torque magnetic random access memory according to another embodiment of the present invention.
[0019] Figure 3 1 is the X-ray diffraction pattern of the nickel-tungsten alloy layer of Preparation Examples 1 to 5.
[0020] Figure 4 This is an image of the magnetic moment reversal observed in Experimental Example 4 using the magneto-optical Kerr effect.
[0021] Figure 5 It is a switching current density diagram of the spin-orbit torque magnetic random access memory of Experimental Examples 1 to 5.
[0022] Fig. 6A This is the SOT flip curve diagram of Experimental Example 2.
[0023] Figure 6BThis is the SOT flip curve diagram of Experimental Example 4.
[0024] Description of Reference Numerals
[0025] 100, 200: Spin-orbit moment magnetic random access memory
[0026] 102, 202: Spin current source alloy layer
[0027] 104: Ferromagnetic free layer
[0028] 106: Insulation layer
[0029] 204: First Area
[0030] 206: Second Area DETAILED DESCRIPTION
[0031] Reference will now be made in detail to exemplary embodiments of the present invention, examples of which are illustrated in the accompanying drawings. Whenever possible, the same reference numerals are used in the drawings and the description to refer to the same or like parts.
[0032] Figure 1 The figure is a cross-sectional schematic diagram of a spin-orbit torque magnetic random access memory according to an embodiment of the present invention.
[0033] Please refer to Figure 1 The spin-orbit torque magnetic random access memory 100 of this embodiment at least includes a spin current source alloy layer 102, a ferromagnetic free layer 104 and an insulating layer 106, wherein the spin current source alloy layer 102 is a nickel-tungsten alloy layer. The "nickel-tungsten alloy layer" in the text refers to an alloy composed of nickel and tungsten, wherein nickel and tungsten are the main components and the rest are inevitable impurities. In one embodiment, the tungsten content of the nickel-tungsten alloy layer is 1at% to 99at%. From the perspective of increasing the spin Hall angle, the nickel-tungsten alloy layer may contain more than 30at% tungsten, such as more than 50at% tungsten or more than 70at% tungsten; the rest is nickel. In one embodiment, the nickel-tungsten alloy layer may contain less than 90at% tungsten. As for the thickness of the spin current source alloy layer 102, it may be more than 4nm, such as more than 10nm, and considering the electrical properties and structural strength, the thickness of the spin current source alloy layer 102 may reach hundreds of nanometers without affecting the spin Hall angle.
[0034] The spin current source alloy layer 102 is formed by, for example but not limited to, forming a nickel-tungsten alloy layer on a substrate (not shown) by sputtering. In one embodiment, the target material used for the sputtering is a nickel-tungsten alloy target. In another embodiment, the sputtering is co-sputtering using a nickel target and a tungsten target, and by adjusting the coating power of the nickel target and the coating power of the tungsten target, nickel-tungsten alloys with different nickel-tungsten composition ratios can be formed.
[0035] Please continue to refer to Figure 1 The ferromagnetic free layer 104 is located on the spin current source alloy layer 102. The material of the ferromagnetic free layer 104 includes metal or metal alloy, which can be listed but not limited to Fe, Co, Ni, Ir, B, Bi, Pt, Pd, Ta, Tb, Mo, Cu, Pt, W, or alloys of two or three of the above metals, such as FeB, CoFe, FePt, FePd, CoPt, CoPd, CoNi, CoFeB or TbFeCo. Figure 1 In the embodiment, the spin current source alloy layer 102 is in direct contact with the ferromagnetic free layer 104, which can achieve the best effect of reducing the write current. However, the present invention is not limited thereto; in other embodiments, other functional film layers can be disposed between the spin current source alloy layer 102 and the ferromagnetic free layer 104, which can still achieve the effect of reducing the write current.
[0036] The ferromagnetic free layer 104 may be formed by, for example but not limited to, sputtering, physical vapor deposition (PVD) or chemical vapor deposition (CVD), such as high density chemical vapor deposition (HDP CVD), low pressure chemical vapor deposition (LPCVD) or plasma enhanced chemical vapor deposition (PECVD), which may be applied to the present invention.
[0037] Please refer again Figure 1 , the insulating layer 106 is located on the ferromagnetic free layer 104. The insulating layer 106 can be a metal oxide or other insulating material suitable as a tunneling barrier; for example, magnesium oxide, aluminum oxide, titanium oxide or a combination thereof. The insulating layer 106 can be formed by, for example but not limited to, sputtering, physical vapor deposition or chemical vapor deposition, such as high-density chemical vapor deposition, low-pressure chemical vapor deposition or plasma-enhanced chemical vapor deposition, which can be applied to the present invention.
[0038] In another embodiment, the spin current source alloy layer 102 (nickel-tungsten alloy layer) is a multilayer film structure, which is composed of several sublayers (not shown), such as 2 to 10 layers. By controlling the different nickel-tungsten composition ratios in each sublayer, the flipping behavior of the ferromagnetic free layer 104 can be controlled. The multilayer film structure is formed by, for example but not limited to, forming the above sublayers layer by layer by sputtering, and the nickel-tungsten composition ratio in each sublayer can be changed by regulating the coating power of the nickel target and the coating power of the tungsten target.
[0039] Figure 2 It is a three-dimensional schematic diagram of a spin-orbit torque magnetic random access memory according to another embodiment of the present invention, in which the same figure marks as those in the previous embodiment are used to represent the same or similar parts and components, and the relevant contents of the same or similar parts and components can also refer to the contents of the previous embodiment and will not be repeated.
[0040] Please refer to Figure 2 The difference between this embodiment and the previous embodiment is that the nickel-tungsten alloy layer has several regions with different polarities. Figure 2 From the above, the spin current source alloy layer 202 in the spin orbit torque magnetic random access memory 200 has a first region 204 and a second region 206 with different polarities, wherein the first region 204 and the second region 206 are both nickel-tungsten alloy layers, but each has a different nickel-tungsten composition ratio. The experimental verification of the present invention shows that different nickel-tungsten composition ratios have different flip polarities, which will be described in detail below.
[0041] Although Figure 2 The first region 204 and the second region 206 are in strip shape, but the present invention is not limited thereto, and the shapes of the first region 204 and the second region 206 may also include block, line or a combination thereof. The spin current source alloy layer 202 is formed by, for example but not limited to, plating nickel-tungsten alloys of different compositions on the first region 204 and the second region 206 using a photomask process, so as to achieve different nickel-tungsten composition ratios in different regions. For example, a mask layer (not shown) is first formed on a substrate (not shown), and then the mask layer is patterned using a first mask process to expose the substrate in the first area 204, and then a nickel-tungsten alloy with a first composition ratio is plated. The mask layer is then removed, and the steps of forming another mask layer (not shown) and performing a second mask process are repeated to cover the first area 204 with the patterned mask layer and expose the substrate in the second area 206, and then a nickel-tungsten alloy with a second composition ratio is plated to form a spin current source alloy layer 202 having a first area 204 and a second area 206 with different nickel-tungsten composition ratios.
[0042] The following experiments are listed to verify the implementation effect of the present invention, but the present invention is not limited to the following contents.
[0043] <Preparation Examples 1 to 5>
[0044] A nickel-tungsten alloy layer was formed on a silicon substrate (thickness of about 675 μm) using a DC magnetron sputtering machine with a nickel target and a tungsten target for co-sputtering. The silicon substrate surface had a 200 nm thermal oxide layer (SiO2). Table 1 below shows different preparation examples and their corresponding coating power ratios.
[0045] Table 1
[0046] Preparation Example Power ratio of nickel target to tungsten target Nickel Tungsten Alloy 1 100:15.7 <![CDATA[Ni 90 IN 10 ]]> 2 50:30.2 <![CDATA[Ni 70 IN 30 ]]> 3 50:71 <![CDATA[Ni 50 IN 50 ]]> 4 25:83.25 <![CDATA[Ni 30 IN 70 ]]> 5 8:100 <![CDATA[Ni 10 IN 90 ]]>
[0047] Then, the nickel-tungsten alloy layers of Preparation Examples 1 to 5 were analyzed by X-ray diffraction to obtain Figure 3 .
[0048] from Figure 3 Available, Ni 90 W10 (10at%W) and Ni 10 W 90 The (90at%W) peak positions are far apart, corresponding to the FCC and BCC textures respectively.
[0049] <Experimental Example 1>
[0050] In order to test the characteristics of the device, a first titanium layer (thickness of about 2 nm) was deposited on a silicon substrate (1 cm×1 cm) whose surface had been oxidized using a DC magnetron sputtering machine, and then a nickel-tungsten alloy layer (thickness of about 6 nm) was formed in the same manner as in Preparation Example 1. Subsequently, a cobalt layer (thickness of about 2 nm) as a ferromagnetic free layer, a magnesium oxide layer (thickness of about 2 nm) as an insulating layer, and a second titanium layer (thickness of about 4 nm) were sequentially formed on the nickel-tungsten alloy layer using a DC magnetron sputtering machine. The first titanium layer can increase the adsorption between the structure and the silicon dioxide on the surface of the silicon substrate, and the second titanium layer can prevent the structure from being oxidized. All of the above layers were deposited in a vacuum of 4×10 -7 After the pressure dropped below mTorr, an argon atmosphere of 3 mTorr was introduced for deposition.
[0051] After the film deposition is completed, the stacked films are made into a Hall cross element with a width of 20μm and a length of 90μm using yellow light lithography and electron etching technology to measure the spin current generated by spin electrons.
[0052] <Experimental Examples 2 to 4>
[0053] The Hall cross element was manufactured in the same manner as in Experimental Example 1, but when forming the nickel-tungsten alloy layer, the method of Preparation Examples 2 to 4 was used instead, and the Hall cross elements of Experimental Examples 2 to 4 were obtained accordingly.
[0054] Then, the element of Experimental Example 4 (Ni-T alloy layer is Ni 30 W 70 ) is placed under a magneto-optical Kerr microscope to observe the reversal of its magnetic moment4. During the measurement process, a current is passed through the current axis of the Hall cross element, and the spin polarized current generated is used to reverse the magnetic moment of the upper ferromagnetic free layer. Due to the Kerr magneto-optical effect, when the magnetic moment is reversed, the image seen under the magneto-optical Kerr microscope will change in brightness, such as Figure 4 shown.
[0055] from Figure 4It can be seen that when the flip is in progress, the image slowly turns black from the white on the far left, indicating that the magnetic moment flips from top to bottom, and when the current direction is reversed, the magnetic moment flips from bottom to top, and the image slowly returns to white from the black in the middle, and the minimum critical current density (critical current density, Jc) required for the spin current to flip the magnetic moment can be calculated. According to the above method, the critical flip current density of the components of Experimental Examples 1 to 5 is tested respectively, and the following can be obtained: Figure 5 .
[0056] from Figure 5 It can be seen that different composition ratios of the nickel-tungsten alloy layer will have different critical switching current densities. For example, the device of Experimental Example 4 (W composition ratio in the tungsten alloy layer is 0.7) has the smallest critical switching current density, which is about 1.8×10 6 A / cm 2 The critical switching current can achieve a lower write current than the currently used beta-W and is more flexible in process conditions, which shows that the nickel-tungsten alloy layer of the present invention has a great competitive advantage as a spin current source material.
[0057] In addition to the reversal current, the intensity of light received by the magneto-optical Kerr microscope is further plotted against the current density of the current axis to obtain Fig. 6A and Figure 6B ,in Fig. 6A Experimental Example 2 (Ni-Tungsten alloy layer is Ni 70 W 30 )’s SOT flip diagram, Figure 6B Experimental Example 4 (Ni-Tungsten alloy layer is Ni 30 W 70 )’s SOT flip diagram.
[0058] from Fig. 6A and Figure 6B It can be seen that the flip curve is clockwise in Experimental Example 2, while the flip curve is counterclockwise in Experimental Example 4. Therefore, it is verified that the different nickel-tungsten composition ratios mentioned above will have different flip polarities. It is estimated that the amount of W will directly affect the crystal structure of the element, thus resulting in different flip properties.
[0059] In summary, the present invention utilizes nickel-tungsten alloy as a spin electronic material to replace the currently common single heavy metal layer. This nickel-tungsten alloy has high flexibility and compatibility in the MRAM process and has a spin Hall angle comparable to that of tungsten metal. In addition, the present invention can also change the device properties, such as the flip polarity of the spin Hall angle, by adjusting the alloy ratio of the nickel-tungsten alloy layer, thus adding another variable condition in practical applications.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A spin-orbit moment magnetic random access memory, characterized in that: include: A spin current source alloy layer, wherein the spin current source alloy layer is a nickel-tungsten alloy layer; A ferromagnetic free layer, located on the spin current source alloy layer; as well as The insulating layer is located on the ferromagnetic free layer.
2. The spin-orbit moment magnetic random access memory according to claim 1, characterized in that: The nickel-tungsten alloy layer is in direct contact with the ferromagnetic free layer.
3. The spin-orbit moment magnetic random access memory according to claim 1, characterized in that: The nickel-tungsten alloy layer contains more than 30 at % of tungsten.
4. The spin-orbit moment magnetic random access memory according to claim 1, characterized in that: The nickel-tungsten alloy layer contains tungsten at less than 90 at %.
5. The spin-orbit moment magnetic random access memory according to claim 1, characterized in that: The nickel-tungsten alloy layer has a plurality of regions with different polarities.
6. The spin-orbit moment magnetic random access memory according to claim 5, characterized in that: The shapes of the plurality of regions include block, line or a combination thereof.
7. The spin-orbit moment magnetic random access memory according to claim 5, characterized in that: The plurality of regions each have a different nickel-tungsten composition ratio.
8. The spin-orbit moment magnetic random access memory according to claim 1, characterized in that: The nickel-tungsten alloy layer is a multi-layer film structure, which is composed of a plurality of sub-layers. The flipping behavior of the ferromagnetic free layer is controlled by controlling the different composition ratios of nickel and tungsten in each of the sub-layers.
9. The spin-orbit moment magnetic random access memory according to claim 8, characterized in that: The multi-layer film structure has 2 to 10 film layers.